O Auto da Compadecida (2000): leitura sobre as mazelas da sociedade sertaneja - Ferreira, Ana Lívia Lourenço (2021)
From the expansion of twentieth century sources, cinema became an investigative possibility for thinking about audiovisual forms of writing historical issues. Considering this assumption, we understand that films elaborate perspectives on events given their production time, that is, more than telling a supposed truth, the works bring to the screen perceptions and points of view that relate to when they were created. Our dissertation aims to think how the film O Auto da Compadecida, a global production directed by Guel Arraes and released in 2000, engenders an elaboration of the ills of the sertaneja society. For such an analysis, we will start from the “Bakhtinian” concept of dialogism, initially thinking about the relationships between the film direction and the origins of the base work for the elaboration of the script, a book with the same name written by Ariano Suassuna in 1955. Also in the course of our investigation we will question the aesthetic composition of the work, comparing the analysis of thematic excerpts and photograms of the film, in order to problematize the social and moral inequalities constituted in the course of the work.